Revisão de livro: Planning Cities with Nature: Theories, Strategies and Methods (Terr@ Plural, 2019)
The productive dialogue among scientists from Latin America, Europe and Asia, who reflect about urban and environmental dilemmas, as well as about possibilities of planning with, and for, the nature of cities in these continents, it is another merit to be highlighted in the book entitled Planning Cities with Nature.